2022
DOI: 10.1039/d2cp01724e
|View full text |Cite
|
Sign up to set email alerts
|

In silicostudy on the effects of disulfide bonds in ORF8 of SARS-CoV-2

Abstract: The COVID-19 epidemic, caused by virus SARS-CoV-2, has been a pandemic and threatening everyone's health in the past two years. In SARS-CoV-2, ORF8 is one of the most important accessory...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 52 publications
(76 reference statements)
2
4
0
Order By: Relevance
“…Concordantly, an early study showed that ORF8 downregulates MHC-I by binding and targeting this immune receptor for lysosomal degradation, as a result protecting SARS-CoV-2-infected cells from CTL killing [11], which was corroborated by other reports [34,70]. In silico analysis further predicted that the main sites in ORF8 which mediate its binding to MHC-I involve positions 39-42 (IHFY), 104-107 (FYED), and 110-112 (EYH), while the deletion of positions 119-120 in the ORF8 of SARS-CoV-2 variant Delta decreases binding compared to wild-type ORF8 [84]. Downregulation of antigen presentation by SARS-CoV-2 was further expanded on by studies from other groups demonstrating that ORF3a, ORF6, and ORF7a are also potent viral antagonists of MHC-I signaling [83,85,86].…”
Section: Downregulation Of Mhc-i To Counter the Ctl Responsesupporting
confidence: 80%
“…Concordantly, an early study showed that ORF8 downregulates MHC-I by binding and targeting this immune receptor for lysosomal degradation, as a result protecting SARS-CoV-2-infected cells from CTL killing [11], which was corroborated by other reports [34,70]. In silico analysis further predicted that the main sites in ORF8 which mediate its binding to MHC-I involve positions 39-42 (IHFY), 104-107 (FYED), and 110-112 (EYH), while the deletion of positions 119-120 in the ORF8 of SARS-CoV-2 variant Delta decreases binding compared to wild-type ORF8 [84]. Downregulation of antigen presentation by SARS-CoV-2 was further expanded on by studies from other groups demonstrating that ORF3a, ORF6, and ORF7a are also potent viral antagonists of MHC-I signaling [83,85,86].…”
Section: Downregulation Of Mhc-i To Counter the Ctl Responsesupporting
confidence: 80%
“…A similar RMSF profile and the considerably higher flexibility of β4-β5 loop region were previously observed in MD studies on ORF8 dimer structures ( Chaudhari et al, 2023 ; Islam et al, 2023 ; Selvaraj et al, 2023 ). These flexible regions were suggested as functional regions that may play major roles in protein-protein interactions in past studies ( Wang et al, 2021 ; Cheng and Peng, 2022 ; Arduini et al, 2023 ). These regions may undergo conformational changes during their functional processes.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the examination of the secondary structure further emphasizes the inherent flexibility of the β4-β5 loop, which serves as a critical mediator of interactions in both the tetrameric and trimeric configurations of ORF8. It has been observed that the manipulation of disulfide bonds can impact the conformation of the β4-β5 loop segments ( Cheng and Peng, 2022 ). Further studies can investigate the ORF8 multimeric forms about the oxidative and reductive environments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The configuration of ORF8 intramolecular disulfide bonds was also suggested to be sensitive to the nature and conformation of the residues adjacent to the Cys residues ( 27 ), which notably are often variant sites such as residues 24, 26, 62, and 84. Finally, an in silico study indicated that the structure of ORF8, especially the loop regions, was greatly influenced by the status of the intramolecular disulfide bonds ( 59 ). The disulfide bonds may therefore represent another structural element associated with conformational adaptability in ORF8.…”
Section: Structure-function Relationshipmentioning
confidence: 99%